Coarse-Grained Modelling of DNA and DNA Self-Assembly - Ouldridge, Thomas E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This thesis presents a novel coarse-grained model of DNA, in which bases are represented as rigid nucleotides. The model is shown to quantitatively reproduce many phenomena, including elastic properties of the double-stranded state, hairpin formation in single strands and hybridization of pairs of strands to form duplexes, the first time such a wide range of properties has been captured by a coarse-grained model. The scope and potential of the model is demonstrated by simulating DNA tweezers, an iconic nanodevice, and a two-footed DNA walker $1 (Bthe first time that coarse-grained modelling has been applied to dynamic DNA nanotechnology.s
A Novel DNA Model -- Methods -- Finite Size Effects -- Structural and Mechanical Properties of Model DNA -- Thermodynamic Properties of Model DNA -- Modelling DNA Tweezers -- Modelling a DNA Walker.
Keywords: Physics; Polymers; Amorphous substances; Complex fluids; Biophysics; Biological physics; Statistical physics; Dynamical systems; Nanotechnology; Physics; Biophysics and Biological Physics; Nanotechnology; Polymer Sciences; Statistical Physics, Dynamical Systems and Complexity; Soft and Granular Matter, Complex Fluids and Microfluidics; Electronic books